Total air content measurements from the RECAP ice core - S. Vudayagiri; B. Vinther; J. Freitag; P. L. Langen; T. Blunier (Climate of the Past)
In this paper, total air content (TAC) of the Renland Ice Cap Project (RECAP) core, drilled in summer 2015, is presented. In principle, TAC is a proxy for the elevation at which the ice was originally formed, as the TAC in ice cores is predominantly influenced by surface air pressure and conditions like temperature and local summer insolation. This, however, presupposes dry sintering of the firn with no surface melting. The RECAP TAC data show incoherently low values in the Holocene Climate Optimum (6 to 9 kyr b2k) and in part of the last interglacial (119 to 121 kyr b2k) originating from melt layers that render the TAC data unfit for paleo-elevation interpretation. Melt instances can, however, be used to reconstruct summer temperatures, and we find that Renland was ∼ 2 to 3 °C warmer compared to today in the early Holocene. Similarly, samples from the previous interglacial hint at summer temperatures that were at least 5 °C warmer than today.